Sharia Aspects and Profitability of Islamic Banks in Indonesia - Media Kusumawardani; Achmad Soediro; Dinda Safira (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
This study examines Sharia aspects that influence the profit of Islamic banks. The Tests use independent variables, namely the components of the Islamicity Performance Index (PSR, ZPR, EDR, DEWR, IsIR, IIR), Maqashid Index, and Islamic Social Reporting, while the dependent variable is proxied to the profitability variable. The data used the annual reports of Islamic banks in Indonesia for 2012 – 2020. The data collection method is purposive sampling, with the amount of data processed being 73 data and statistical testing using statistical data processing software. The results of the study show that Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), Islamic Income (IsIR), Islamic Investment (IIR), Maqashid Index, and Islamic Social Reporting (ISR) have a positive effect on Profitability, while the Welfare Ratio (DEWR) has a negative impact on profit. The statistical results show that all the hypotheses in this study are accepted.